6C.06: GENES INVOLVED IN BLOOD PRESSURE RESPONSE TO ACUTE AND CHRONIC SALT MODIFICATIONS. (June 2015) - Gatti, G.; Lanzani, C.; Citterio, L.; Messaggio, E.; Carpini, S. Delli; Simonini, M.; Pozzoli, S.; Casamassima, N.; Zagato, L.; Rampoldi, L.; Hamlyn, J.M.; Manunta, P.
Abstract : Objective: A moderate reduction in salt intake reduces BP in most but not all individuals. Identification of genetic loci combination is a difficult task. Recently, the uromodulin (UMOD) gene has been associated with renal damage and hypertension. Design and method: Present study evaluated the role Endogenous Ouabain (EO), polymorphisms in a candidate gene related to its synthesis, Lanosterol Synthase (LSS), and in UMOD in variability of response to acute and chronic body Na variations. Acute Na load protocol in 608 naïve hypertensive patients (NHP) was carried out. 183 NHP followed a low Na intake diet for 15 days. UMOD and LSS gene polymorphisms have been tested. Results: Acute protocol: NHP carrying UMOD GG/LSS AA display a pressure-natriuresis curve with negative slope (Salt Resistant), while those with UMOD AA/LSS AA showed a right shift of pressure-natriuresis curve (Salt Sensitive, upper panel). Low Na intake: In a dietary compliant group with the reduction of UNa excretion, a direct (β=0.213) relationship (p = 0.026) between the change in EO and BP was found. When LSS and UMOD gene variants were analyzed together, a significant interaction was detected: those patients homozygous for the A alleles of both gene variants displayed a 5-fold greater decline in SBP than patients carrying other allele combinations (lower panel). Figure. No caption available. Conclusions: We identify a genetic interaction that characterized a subgroup of patients. In this pathway UMOD may affect renal tubular Na excretions, whereas LSS affects vasoconstrictor activity modulating circulating EO levels. This new pathway is relevant for blood pressure response during both acute and chronic salt modification.